DANO OXIDATIVO HEPÁTICO, RENAL E ESPLÊNICO DE CAMUNDONGOS B6 SUBMETIDOS A PROTOCOLO DE PERITONITE - Dos Santos, Tainá Mafalda; Heck, Thiago Gomes; Sulzbacher, Maicon Machado; Dos Santos, Analú Bender; Goettems, Pauline Brendler (Salão do Conhecimento, 2013)
Resumos